Comparison of the cleaning capacity of Mtwo and ProTaper rotary systems and manual instruments in primary teeth - Mohammad Reza Azar; Laya Safi; Afshin Nikaein (Wolters Kluwer Medknow Publications, 2012)
Background: Root canal cleaning is an important step in endodontic therapy. In order to develop better techniques, a new generation of endodontic instruments has been designed. The aim of this study was to compare the effectiveness of manual K-files (Mani Co, Tokyo, Japan) and two rotary systems-Mtwo (Dentsply-Maillefer, Ballaigues, Switzerland) and ProTaper (VDW, Munich, Germany)-for root canal preparation in primary molars. Materials and Methods: India ink was injected to 160 mesiobuccal and distal root canals of mandibular primary molars. The teeth were randomly divided into three experimental groups and one control group. In each experimental group, either manual instruments (K-files) or rotary instruments (Mtwo or ProTaper) were used to prepare root canals. After cleaning the canals and clearing the teeth, ink removal was evaluated with a stereomicroscope. Statistical analysis was done with Kruskal-Wallis and Friedman tests. Results: There were no significant differences in cleaning efficiency between manual and rotary instruments. Only ProTaper files performed significantly better in the coronal and middle thirds than in the apical third of the root canal. Conclusion: Manual K-files and the Mtwo and ProTaper rotary systems showed equally acceptable cleaning ability in primary molar root canals.